THE OPEN QUESTION ARGUMENT AND THE POSSIBILITY OF REDUCTIONISM. - Vasilionytė, Ieva (Problems / Problemos)
In this paper I am interested in which reductionist positions are blocked, and on what grounds, by the Open Question Argument (OQA) both historically and by its contemporary guises. I single out four most salient interpretations of the OQA and analyze their impact on the possibility of reductionist theories of evaluative properties. It will be suggested that the OQA poses a serious threat to semantic naturalism about moral terms, but does not block the possibility of metaphysical ethical naturalism (though possibly condemns it to a certain schizophrenia).